Investigating the Impact of Trade on Poverty Reduction in a Small Island Economy. Issue 4 (2nd October 2022) - Fauzel, Sheereen
Abstract: The contribution of international trade to economic development has long been debated. While comparative advantage theorists have claimed that trade will benefit a country at large and that this development will help the poor, the general concept is still being debated by social economists attributing development to human development. Discussions in this regard have tended to centre on the extent to which international trade can bring social benefits in terms of job creation and poverty reduction. Aside from this, empirical studies have shown that trade can harm the poor. Trade openness can increase poverty through the increase of inequality in developing countries. Given the fact that there is considerable disagreement in this field, this paper carried out a quantitative investigation of the impact of trade on poverty reduction. The case of the small island of Mauritius is considered over the time period of 1990–2017. Using a dynamic econometric technique, namely, the vector error correction model, the study found that trade reduces poverty in the long, rather than the short run. Moreover, the study also shows that economic growth as well as education are important to alleviate poverty in the country. Hence, it is recommended that the government adopt an export-led poverty Reduction Programme, which will integrate poor communities into trade. Other social protections and social policies like the provision of welfare benefits are recommended to reduce poverty level in the country.